Recommendations and guidelines for perinatal practice - (:unkn) unknown (WALTER DE GRUYTER GMBH, 2007)
The purpose of this document is to expand the 1995 ISTS/COMBO Declaration of Rights which was initially produced to promote awareness of the special needs of multiple birth infants, children, and adults. It addresses the clinical and ethical dimensions of perinatal care of multiple pregnancy. The ad hoc committee was chaired by Isaac Blickstein. The following individuals were present (in alphabetical order): Birgit Arabin (Zwolle, Netherlands/Berlin, Germany), Isaac Blickstein (Rehovot, Israel), Frank A. Chervenak (NY, USA), Zehra Nese Kavak (Istanbul, Turkey), Louis G. Keith (Chicago, USA), Eric S. Shinwell (Rehovot, Israel) and Yves Ville (Paris, France). Secretary of the meeting was Alin Basgul (Istanbul, Turkey). This statement was endorsed by the International Society of Twin Studies (Ghent, Belgium, June, 2007) and by the World Association of Perinatal Medicine (Florence, Italy, September, 2007).